A New Variant of Posterior Canal Benign Paroxysmal Positional Vertigo: A Nonampullary or Common Crus Canalolithiasis - Sertac Yetiser (Case Reports in Otolaryngology)
Clockwise or counterclockwise, rotational, upbeating nystagmus is seen in patients with posterior canal benign paroxysmal positional vertigo during left or right head-hanging test, respectively. Rotating of nystagmus in opposite direction to the ear tested or even reversal of initial positioning rotational nystagmus is not usual and has never been reported before. We propose a new variant of posterior canal benign paroxysmal positional vertigo due to unusual behavior and location of the otoliths inside the membranous labyrinth. Unexpected rotational direction may lead to confusion about the site. The examiner should be aware of this abnormal or atypical variant of posterior canal benign paroxysmal positional vertigo.